Pigeon bean allelopathy on the germination and development of carrot seedlings - Dotto, L.; Silva, V. N.; Ribeiro, G.; Severo, I. K. (Scientific Electronic Archives, 2018)
Carrot is an edible tuberous root with high economic value in Brazil. Carrot seeds may present uneven germination due to the presence of inhibitors in the epithelium. The presence of cover crops in the growing area may generate allelopathic compounds, with the potential to inhibit or stimulate germination of cultivated species. The work objective was verifyingÂ effect of pigeon bean extract levels on germination and development of carrot seedlings. The research was conducted in a completely randomized design, in a 3x5 factorial scheme (cultivars,Danvers, Flakker Giant and Nantes Milena and extract concentrations, 0, 25, 50, 75 and 100%). Were evaluate germination (first germination count, speed and final percentage), seedling root length and seedling dry mass. The data obtained were submittedÂ toÂ variance and regression analysis.